Remote monitoring of lands, the soil cover of wich is disturbed due to arbitrary amber mining - Zayachkivska, B.; Paliy, A. (Land Management, Cadastre and Land Monitoring, 2024)
Illegal amber mining has become an environmental disaster in Rivne region. In particular, since 2014, amber has been illegally mined in the Varas district of the Rivne region, near the village of Zelene. Local residents are witnessing the destruction of the ecological and recreational value of forests, which until recently were places for them to rest, pick mushrooms, berries, etc. In order to extract amber, forests are cut down, the unique ecosystem is destroyed, the soil cover is disturbed, the water regime of the soil is changed, etc. Thus, "amber fever" causes significant damage to land resources. Land disturbance due to amber mining has caused significant economic losses and irreversible environmental changes. This research topic is timely, relevant and important from the point of view of ensuring the sustainable development of territories. The purpose of this study is to monitor lands whose soil cover has been disturbed as a result of unauthorized amber mining by means of remote land sensing (RLS) and geospatial analysis. RLS methods in combination with field observations of the research object confirm the obtained results. As a result of the illegal mining of amber within the experimental area of 40 hectares, a violation of the soil cover in the amount of 46.25% of the total area was found. The scientific work has a valuable practical result and makes it possible to remotely determine the location, time periods and extent of land cover violations caused by arbitrary amber mining with high accuracy using space cameras. Such a research area is representative, and the research results can be used to develop recommendations and strategies for environmental protection and sustainable development of territories. Key words: amber mining; soil cover disturbance; monitoring of land resources; geospatial analysis; retrospective analysis; illegal mining; consequences of amber mining; lands, soil cover of wich is disturbed.